The Effect of Religious Music Therapy on the Intensity of Menstrual Pain in Teenage Girls in Daarul Muttaqien II Islamic Boarding School Tangerang - Lilis Komariah; Azizah Al Ashri Nainar; Cut Funny Sepdiana (Universitas Muhammadiyah Tangerang, 2020)
Adolescence is a transition from childhood to adulthood which includes biological, psychological and social changes. During menstruation there will be problems or complaints such as dysmenorrhea. Meanwhile, menstrual pain (dysmenorrhea) is a physical disorder that is very prominent in women who are experiencing menstruation in the form of pain in the stomach. This study aims to determine the effect of religious music on the intensity of menstrual pain in class X adolescents at the Daarul Muttaqien II Modern Islamic boarding school, Tangerang. The research design used was a quasy-experiment with a pre and post-test design without control (self-control). Collecting data using the NRS observation sheet and pain measurement that has been tested for validity and reliability. The sample consisted of 35 respondents who were taken by consecutive sampling technique. This study showed that 68.6% of respondents had mild pain, while 31.4% of respondents had no pain. The results of the Wilcoxon statistical test showed that there were significant differences in the level of knowledge before and after religious music therapy with a value of p = 0.001 (p <0.05). This research is expected to be developed in further research and can be used as a reference by increasing the number of samples and variables as a comparison.Keywords: Effect of Music Therapy, Menstrual Pain